Food justice: cultivating the field - Charlotte Glennie; Alison Hope Alkon (Environmental Research Letters, 2018)
This article provides an evidence-based review of the growing field of food justice, which seeks to understand how inequalities of race, class and gender are reproduced and contested within food systems. Analyzing a database of peer-reviewed articles and books related to food justice in the US context ( n  = 200), we find that food justice is a highly interdisciplinary research area organized around three central axes: social movement activism, the development of alternative food practices, and analyses of inequalities in conventional and alternative food systems. Especially since 2011, the rate of new scholarship has increased, along with increased attention from policymakers and the public to the issues of inequality in the food system. This field has developed somewhat independently of work in the physical sciences quantifying and evaluating the sustainability of local food systems, instead focusing more on social science concepts such as historic and present-day inequalities and the role of policy. However, there is room for convergence, especially as our analysis points to agro-ecology and land tenure as areas of growing interest. Considering this recent growth and potential for collaboration with physical scientists, we reflect on the development of the field to date by characterizing the field of food justice research, asking what is missing, and suggesting new directions.